Stereotype contents, emotions, and public attitudes: How do Chinese people stereotype nations and national groups?. (January 2022) - Liang, Lemeng; Jin, Yongai; Zhou, Jie; Xie, Yu
Previous studies have provided various explanations for people's attitudes toward foreign countries, but we still know very little about causal mechanisms of attitude formation. In this study, we propose that stereotypes play an important role in affecting individuals' attitudes toward foreign countries. Drawing on survey data collected in 2019 and 2020 in China, we apply the stereotype content model to analyze Chinese people's attitudes toward five countries: the United States, Japan, India, Tanzania, and China itself. Our analyses show that: (a) Chinese respondents stereotype the five countries differently along two dimensions—warmth and competence—with the extremely high evaluations of China itself, indicating in-group favoritism; (b) warmth–competence combinations are closely linked with four emotions—admiration, envy, pity, and contempt—but are also affected by historical and cultural contexts; (c) stereotype contents can predict favorable attitudes toward foreign countries, with warmth stereotypes being more predictive than competence stereotypes; emotions can also predict favorability; and (d) stereotypes of countries are similar to stereotypes of persons from those countries, as is the case for emotions and attitudes.